Microorganisms associated with disease symptoms in native fruit trees from a subtropical climate in northwestern Rio Grande do Sul, Brazil - Araujo, Betina Lopes Machado de; Bez, Felipe Suzin; Bueno, Thalles da Rosa; Drawanz, Bruna Bento; Antunes, Luidi Eric Guimarães; Bocchese, Carla Azambuja Centeno (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
This research aimed to diagnose the microorganisms associated with symptoms of diseases that may compromise the productive potential of these fruit trees. In the municipality of São José do Ouro / RS, 26 samples of 13 species of native fruits were collected: Rubus erythrocladus Mart., Psidium cattleyanum Sabine, Annona crassiflora Mart., Araucaria angustifólia Bertol., Butia eriospatha Mart. ex Drude Becc., Eugenia involucrata DC., Acca sellowiana [O. Berg] Burret, Eugenia pungens O. Berg., Campomanesia xanthocarpa Berg., Myrcia bombycina Berg. Kiaersk, Myrciaria cauliflora O. Berg., Passiflora edulis Sims. F. Flavicarpa Deg. e Eugenia uniflora L, all presenting characteristic symptoms of diseases with potential risk of damage to fruit trees. The analysis and identification of microorganisms present in the lesions of the samples was carried out using a stereomicroscope and microscope for observation and comparison of the structures based on the bibliography. All 26 samples showed symptoms of leaf spots. Eleven genera of microorganisms were identified, of these 3 genera predominated: Colletotrichum sp. (18.19%); Cephaleuros sp. (15.15%) and Puccinia sp. (15.15%). The predominant pathogens in native fruit trees in northwestern Rio Grande do Sul were two fungi, Colletotrichum sp. and Puccinia sp., and an alga, Cephaleurus sp.